Promotion of democracy and foreign policy in India - Wagner, Christian (2009)
Zusammenfassung: The promotion of democracy has been one of the highest priorities of Western foreign and development policy for many years. India is the largest democracy and is increasingly perceived as an important international actor by Germany, Europe and the USA. Given their common democratic values, the question arises as to whether India can be a partner to the West in the promotion of democratic regimes.The promotion of democracy plays only a subordinate role in Indian foreign policy. India's national interests are determined by security considerations in respect to China and Pakistan, trade and economic motives, as well as by the need to secure energy and resources. India has only a limited interest in promoting democracy in the Western sense, as a foreign policy instrument for the transformation of authoritarian regimes. Following the improvement of relations with the USA in the 1990's, some first approaches towards the promotion of democracy have been developed. Democratic development is propagated in a very broad, multilateral context or in a very narrow bilateral form as development cooperation. India thus remains a difficult partner in German and European politics in respect to the promotion of democracy. Nevertheless, since India's democratic know-how can be of advantage in the building up of new democracies, the dialogue with India concerning this issue should be intensified